ARGUMENTATION SKILLS AND SELF-REGULATION OF STUDENTS USING PROBLEM BASED LEARNING COMBINED WITH DEBATES BASED ON SOCIOSCIENTIFIC ISSUES ON ENVIRONMENTAL CHANGE MATERIAL - Anie Yuni Widyastuti; Harlita Harlita; Meti Indrowati (EDUSAINS, 2024)
Lack of self-confidence and self-monitoring to think, act and communicate scientifically are related to argumentation skills. This study aimed to determine differences: (1) students' argumentation skills, (2) students' self-regulation, (3) argumentation skills and students' self-regulation using Problem Based Learning (PBL) combined with debates based on Socio-scientific issues (SSI) on environmental change material. The method used is a quasi-experiment with a posttest only control group design. The population in this study was class X SMA N 2 Karanganyar 2022/2023, and the sample used was class XE2 and class XE7. The sample technique used is cluster random sampling. Collecting data on argumentation skills uses a test, while collecting data on self-regulation uses a questionnaire. The data analysis technique used the t test and teh manova test. It was concluded that there were significant differences: (1) students' argumentation skills, (2) students' self-regulation, (3) argumentation skills and students' self-regulation using Problem Based Learning (PBL) combined with debates based on Socio-scientific issues (SSI) on environmental change material. The research results can be used as a reference related to PBL learning, debate method, argumentation skills and students’ self-regulation abilities